Pengaruh Peran Kepemimpinan Dan Disiplin Kerja Terhadap Kinerja Karyawan Alfamart Di Kecamatan Mustika Jaya Kota Bekasi - Tania Annisa; Dadan Ahmad Fadili (Peneliti.net, 2022)
This study aims to describe, examine and analyze the influence of the role of leadership and work discipline on the performance of Alfamart employees in Mustika Jaya District, Bekasi City. The sample in this study amounted to 112 using the Non Probability Sampling sample collection technique with a saturated sample. The data analysis techniques used are scale range analysis and path analysis using the Method of Successive Interval (MSI), Microsoft Office and SPSS 22. The results of simultaneous influence the role of leadership and work discipline on employee performance is 62%, while the remaining 38% is the influence of other variables not examined.